Benzoxepin-Type Selective Estrogen Receptor (ER) Modulators and Downregulators with Subtype-Specific ERalpha and ERbeta Activity - O'Boyle, Niamh (My University, 2018)
The two nuclear estrogen receptors (ERα and ERβ) mediate the biological effects of the estrogen hormones and ERα is an attractive therapeutic target for diseases including breast cancer and osteoporosis. Estrogens are known to have tissue selective effects, and there is considerable interest in the therapeutic use of selective estrogen receptor modulators (SERMs). ERα is an important target for drugs such as tamoxifen and fulvestrant. There is ongoing debate about the role of ERβ in cancer. Three series of ER-ligands based on the benzoxepin scaffold structure were synthesized—series I containing an acrylic acid, series II with an acrylamide and series III with a saturated carboxylic acid substituent. These compounds were shown to be high affinity ligands for the ER with nanomolar IC50 binding values. Series I acrylic acid ligands were generally ERα selective. In particular, compound 13e featuring a phenylpenta-2,4-dienoic acid substituent was shown to be antiproliferative and downregulated ERα and ERβ expression in MCF-7 breast cancer cells. Interestingly, from series III, the phenoxybutyric acid derivative compound 22 was not antiproliferative and selectively downregulated ERβ. A docking study of the benzoxepin ligands was undertaken. Compound 13e is a promising lead for development as a clinically relevant SERD, whilst compound 22 will be a useful experimental probe for helping to elucidate the role of ERβ in cancer cells.
26th Annual GP2A Medicinal Chemistry Conference & 32nd Journ?es Franco-Belges de Pharmacochimie
PUBLISHED
Asnelles sur Mer, Normandie, France
Keywords: Estrogen receptors; Breast cancer; Osteoporosis; Selective estrogen receptor modulators; Cancer; ANTI-CANCER DRUG DESIGN; Chemistry of drug receptor interactions; DRUG DISCOVERY; Design, synthesis and mechanism of action of novel anti-estrogenic compounds; ESTROGEN; Estrogen Receptor; Molecular modelling of Estrogen Receptor antagonists